Management of Dyslipidemia and Hypertension – Journey Mapping in the Philippines - Atilano, Alberto A; Llanes, Elmer Jasper B.; Ona, Deborah Ignacia D.; Brizuela, Grace E. (Acta Medica, 2022)
Literature was reviewed semi-systematically with the purpose of generating Philippines-specific data for the patient journey stages for dyslipidemia and hypertension, namely, awareness, screening, diagnosis, treatment, adherence, and control. A structured search was conducted on EMBASE and MEDLINE databases for studies published in English in the last 10 years, whose full text was available. An unstructured search was conducted on Google, and websites of health ministries and international organizations, without any limits. The last search was run for dyslipidemia on 12.11.2019 and for hypertension on 28.07.2020. For dyslipidemia, six records out of 590 records were retrieved, and for hypertension, seven records and one unpublished conference presentation out of 160 records retrieved, were included in the final synthesis. The review estimated that in the Philippines, the prevalence of dyslipidemia was 38.8%, while 59.0% of patients were undergoing treatment, with 44.2% of patients achieving control. Prevalence of hypertension was 27.5% and estimated rates at different stages of patient journey were- awareness- 61.5%, screening- 3.2%, diagnosis- 39.7%, treatment- 65.4%, adherence- 57%, and control- 57.6%. Potential contributory factors for low assessment rates and suboptimal management include low doctor-to-population ratio, inadequate time for screening and counseling, absence of locally validated tools for cardiovascular screening, low awareness and utilization of clinical practice guidelines, and some misperceptions of current treatment recommendations. Effective training of physicians, patient education initiatives, and multi-sectoral coordination are some of the recommendations to improve the status of management of dyslipidemia and hypertension in the Philippines.